Mewujudkan Bayi Sehat melalui Kelas Era Baru (Perawatan BBL) pada Kader dan Ibu Hamil - Wahyuni Wahyuni; Irmasanti Fajrin (Caradde)
This activity aims to empower women, enhance the knowledge, and improve the skills of cadres and pregnant women regarding newborn care. The ERA BARU program employs a mentorship approach involving cadres and pregnant women through three stages: preparation (permissions, initial visits, educational materials), implementation (introductions, knowledge and skills assessments, Focus Group Discussions), and evaluation (outcome evaluation and reporting). Success is measured using SPSS 16 for analyzing improvements in knowledge and skills before and after the program. The results of this initiative indicate that the ERA BARU classes have had a positive impact by significantly increasing the knowledge and skills of both cadres and pregnant women in newborn care. Significant improvements are evident across all categories, with cadres showing higher increases compared to pregnant women. Thus, this initiative enhances the knowledge and skills of cadres and pregnant women in newborn care and empowers women through cadre mentorship during education.